2020
DOI: 10.3390/ijerph17207604
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Public Health Promotion Behavior: Evidence from Repurchasing Health Foods for Improving Gastrointestinal Tract Functions

Abstract: Researchers believe that health foods can promote health and that the consumption of health foods can effectively help people to maintain their health. This study mainly adopted the health belief model (HBM) integrated with perceived behavioral control to investigate the repurchase behavior of consumers with regard to health foods that improve gastrointestinal functions. We obtained 550 valid questionnaires from consumers who had purchased gastrointestinal health foods and conducted structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Rezai, Teng, Shamsudin, Mohamed, and Stanton (2017) noted that consumers tend to have high intentions to purchase natural functional foods if they believe they could improve their health conditions. Similarly, the positively significant effect of perceived benefits (PB) on the PI of functional foods is also remarked in the literature (Natarajan et al, 2022;Lee, Wei, Wu, & Hsieh, 2020). In agreement with the literature, HC and PB are projected to significantly determine functional foods' PI.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Rezai, Teng, Shamsudin, Mohamed, and Stanton (2017) noted that consumers tend to have high intentions to purchase natural functional foods if they believe they could improve their health conditions. Similarly, the positively significant effect of perceived benefits (PB) on the PI of functional foods is also remarked in the literature (Natarajan et al, 2022;Lee, Wei, Wu, & Hsieh, 2020). In agreement with the literature, HC and PB are projected to significantly determine functional foods' PI.…”
Section: Introductionsupporting
confidence: 79%
“…For example, in this study, the functional foods buyers will likely purchase functional foods if they perceive that it is easy to get them without additional effort and costs. Empirical studies have supported this supposition, whereas PBC's positive effect on PI is well documented in the literature (Lee et al, 2020;Liu et al, 2021;Prakash et al, 2023). For instance, Sumaedi and Sumardjo (2021) revealed that PBC positively impacted traditional functional foods in Indonesia.…”
Section: Pbc On Pimentioning
confidence: 96%
“…The concept of perceived barriers pertains herein to the various hindrances or difficulties that individuals attribute to the process of adopting a vegan diet (Younas et al, 2023). In a study, Lee et al (2020) postulate that barriers play a crucial role in predicting individuals' intentions and beliefs associated with a particular behavior. Perceived barriers concerning the adoption of a vegan diet encompass a range of factors that individuals may perceive for adopting a vegan diet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars have used perceived susceptibility and perceived severity in health belief models to measure the perceived risk of diseases. It has been found that consumers’ perceived susceptibility and perceived severity of common health problems can significantly stimulate their intentions to purchase healthy foods [ 48 , 49 ]. Moreover, two health beliefs based on perceived susceptibility and perceived severity of diseases can significantly and positively influence users’ disease-related preventive behaviors [ 50 , 51 ].…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%